PURSUING SUSTAINABILITY: ENVIRONMENTAL COMMUNICATION AND THE COMMUNITY'S ROLE IN ENHANCING BANJARMASIN'S RIVER ECOSYSTEMS - Waluyo, Bambang Dwi; Buwono, Achmad Bayu Chandra (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2023)
As one of the most modern cities in South Kalimantan, Banjarmasin has emerged as a popular place to visit for residents of the surrounding rural regions. Is it true that the city of Banjarmasin has developed into a secure location from an economic, social, and environmental standpoint? This paper attempts to look at the cognitive behavior of the people of Banjarmasin in regard to the messages that were communicated by the Sahabat Sungai community. This is done by attempting to understand the strategies that were carried out by the Sahabat Sungai community through environmental communication. Aside from that, we also need to pay attention to the ways in which residents living near the river in Banjarmasin are attempting to address the deteriorating conditions along the river.